Structure of developmental gene regulatory networks from the perspective of cell fate-determining genes - Martín, Mercedes (Transcription, 2016)
The core of gene regulatory networks (GRNs) is formed by transcription factors (TF) and cis–regulatory modules (CRMs) present in their downstream genes. GRNs have a modular structure in which complex circuitries link TFs to CRMs to generate specific transcriptional outputs.(1) Of particular interest are those GRNs including cell fate-determining genes, as they constitute developmental switches which activity is necessary and sufficient to promote particular cellular fates. Most of the genetic analysis of developmental processes deals with the composition and structure of GRNs acting upstream of cell fate-determining genes, as they are best suited for genetic analysis and molecular deconstruction. More recently, the application of a variety of in vivo, computational and genome-wide approaches is allowing the identification and functional analysis of GRNs acting downstream of cell fate-determining genes. In this review we discuss several examples of GRNs acting upstream and downstream of cell fate-determining genes, including other TFs which activity pervade across both regulatory networks.